Analysis and selection of the parametric profile of a powerplant engine for a light trainer aircraft - Loginov, Vasiliy; Ukrainets, Yevgeniy; Kravchenko, Igor; Yelansky, Аlexandr (Eastern-European Journal of Enterprise Technologies, 2019)
The relevance of this study is predetermined by the improvement to the fuel efficiency of an aircraft and, as a consequence, by the reduced cost of the life cycle of an aircraft engine, which is part of a power assembly at the training aircraft the type of DART-450. We have theoretically substantiated the flight-technical and economic characteristics of a modern light aircraft for training flying personnel. Underlying the research methods is a set of parameters, characteristics and indicators, which generally reflect the technical-economic perfection of engine in the powerplant of the technical system «powerplant ‒ airframe» at a light training aircraft. The scientific novelty of this research is in the formation of a new parametric shape of a turboprop engine for the powerplant of a light training aircraft the type of DART-450, taking into consideration the modeling of the predefined flight cycle of an aircraft and the life cycle of the engine. Numerical study has established that the maximum flight range of aircraft with different engines at the same takeoff weight is largely determined by a fuel reserve, rather than the efficiency of fuel consumption. Therefore, an engine with the lowest capacity has the advantage in all characteristics except for a takeoff distance, which is the shortest for an aircraft with the engine of maximum power. The results have substantiated that in order to perform tasks related to training flight personnel it is appropriate to install the engine AI-450SR, which has the lowest life cycle cost. It is obvious that a given aircraft with the installed engine will have the lowest cost per flight hour. However, to perform reconnaissance and strike missions at an aircraft the type of DART-450, it is advisable to install the engine AI-450SR. To perform only the strike missions at an aircraft the type of DART-450, it is expedient to install the engine MS-500V-S, which has more power than the considered motors